2023
DOI: 10.1021/acsenergylett.3c00439
|View full text |Cite
|
Sign up to set email alerts
|

A 2.6 V Flexible Supercapacitor Based on Al-MnO2-Na2SO4//AC-KOH with High Specific Energy

Abstract: In this work, we have synthesized Al-doped MnO2 nanoparticles (Al-MnO2) by rapid coprecipitation followed by hydrothermal and heat treatment. Al-MnO2 shows a specific capacitance of 301.8 F g–1 at 1 A g–1 in a sample of 14% Al-MnO2-260 °C. The specific capacitance still remains at 206 F g–1 at 20 A g–1. It also shows a good cycling stability with no capacitance degradation after 5000 cycles. More importantly, a new type of supercapacitor, Al-MnO2|PVA-Na2SO4//PVA-KOH|AC, has been designed using a Na2SO4-poly­(v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Observing the entire XRD pattern, it can be seen that the doping of Al 3+ /Fe 3+ expands the lattice spacing of MnO 2 without altering its crystal structure. 36,43,44 According to formulas 3–6, the average grain size ( D ), dislocation density ( δ ), microstrain ( ε ), and stacking fault probability ( α ) of all materials were calculated using the experimental XRD data. 45 The structural parameters of MnO 2 , Al-MnO 2 , and Fe-MnO 2 are shown in Table 1.where θ is Bragg's angle of a particular diffraction peak and λ represents the wavelength of Cu Kα radiation (0.15406 nm).…”
Section: Resultsmentioning
confidence: 99%
“…Observing the entire XRD pattern, it can be seen that the doping of Al 3+ /Fe 3+ expands the lattice spacing of MnO 2 without altering its crystal structure. 36,43,44 According to formulas 3–6, the average grain size ( D ), dislocation density ( δ ), microstrain ( ε ), and stacking fault probability ( α ) of all materials were calculated using the experimental XRD data. 45 The structural parameters of MnO 2 , Al-MnO 2 , and Fe-MnO 2 are shown in Table 1.where θ is Bragg's angle of a particular diffraction peak and λ represents the wavelength of Cu Kα radiation (0.15406 nm).…”
Section: Resultsmentioning
confidence: 99%
“…As far as the application of gel polymers as electrolytes in supercapacitors is concerned, there are several advantages over other classes of electrolytes [45]. With the rapid growth in portable electronic devices, there is an urgent need to develop wearable, flexible energy storage devices like flexible supercapacitors (FSCs) [46][47][48][49][50]. To achieve high performances out of supercapacitors, the development of better electrodes, housing, separators, and other flexible components are crucial; however, this section is dedicated to the development of gel electrolytes to enhance the electrochemical performances of supercapacitors.…”
Section: Hybrid Polymer Gel Electrolytes For Supercapacitorsmentioning
confidence: 99%
“…Extensive research has demonstrated the enhanced intrinsic properties of energy storage materials through the introduction of heteroatom doping or functional group modification. This is commonly achieved through various methodologies, including high temperature sintering, 1,2 co-precipitation, 3,4 hydrothermal reactions, 5–7 vapor deposition (CVD/PVD), 8,9 chemical reactions, and other similar approaches. These techniques lead to improvements in specific capacity, initial efficiency, and rate capability of energy storage materials by inducing the formation of defects, vacancies, active sites, 10 etc.…”
Section: Introductionmentioning
confidence: 99%